Media Pembelajaran KKPI Berbasis Android Pada Siswa Smk Kelas X - Yuslina Gultom Universitas Bina Sarana Informatika; Ahmad Fauzi STMIK Nusa Mandiri; Rian Septian Anwar Universitas Bina Sarana Informatika; Kristine Harefa Universitas Bina Sarana Informatika (Indonesian Journal of Networking and Security (IJNS), 2019)
Abstract - Teaching transformation using technological advances can help educators work as realy educators and help foster interest in learning independently, as well as help students' creativity to learn anywhere and anytime, without being limited by space and time. With current technological advances, the emergence of learning software for children or adults, one of which is the KKPI learning application for grade X students of computer engineering vocational high schools and networks based on Android. KKPI Learning Application for grade X Vocational High School Computer Engineering and Networking Students Based on Android is an android application made with Android Studio software that uses the Java programming language. This application serves to provide a short lesson about KKPI subject matter to its users and is also provided with practice questions so that the material presented by this application can be accepted and understood by its users. In this application there are summaries of KKPI material specifically for grade X students in Vocational High Schools and Senior High Schools. Thus this application can be expected to attract the interest of vocational students to be able to continue learning anywhere and anytime. Keywords : Learning Media, Android, Learning Applications Abstrak - Transformasi pengajaran dengan menggunakan kemajuan teknologi dapat membantu tugas pendidik sebagai tenaga pendidik dan membantu menumbuhkan minat belajar secara mandri, serta membantu kreatifitas anak didik untuk belajar dimana saja dan kapan saja, tanpa dibatasi ruang dan waktu. Dengan kemajuan teknologi saat ini memyebabkan bermunculannya software pembelajaran bagi anak – anak ataupun orang dewasa salah satunya aplikasi pembelejaran KKPI untuk siswa kelas X sekolah menengah kejuruan teknik komputer dan jaringan berbasis android. Aplikasi Pembelajaran KKPI Untuk Siswa Kelas X Sekolah Menengah Kejuruan Teknik Komputer dan Jaringan Berbasis Android ini merupakan aplikasi android yang dibuat dengan software Android Studio yang menggunakan bahasa pemograman java. Aplikasi ini berfungsi untuk memberikan pelajaran singkat mengenai materi pelajaran KKPI kepada penggunanya dan juga disediakan dengan latihan – latihan soal agar materi yang disampaikan oleh aplikasi ini dapat diterima dan dipahami bagi para penggunanya. Didalam aplikasi ini terdapat rangkuman – rangkuman materi KKPI yang di khususkan untuk siswa kelas X di Sekolah Menengah Kejuruan maupun Sekolah Menegah Atas. Demikian aplikasi ini dapat diharapkan menarik minat siswa SMK untuk bisa terus belajar dimana saja dan kapan saja. Kata Kunci: Media Pembelajaran, Android, Aplikasi Belajar